CARACTERIZATION OF A SPIRONOLACTONE SESQUITERPENE á-METILENICA FROM Ambrosia arborescens Miller AND EVALUATION OF THEIR BIOLOGICALACTIVITY IN Tripanosoma cruzi - Cano de Terrones, Teresa (2014)
Ambrosia arborescens Miller, commonly known as “marco” is a South American aromatic plant found mainly in the Department of Arequipa at the Peruvian Andes. The study of the chemical constituents of Ambrosia arborescens, aerial portion, allowed obtaining a spironolactone sesquiterpene. For its separation and isolation I use chromatographic methods of column, cap it dies and Chromatography liquidates of high efficiency. Structural elucidation was done with spectroscopic methods: protonic nuclear magnetic resonance,(1H-NMR), carbon-13 (13C-NMR), infrared spectroscopy (IR) and mass spectrometry (MS). To determine stereochemistry and conformations two-dimensional spectroscopic experiments were: COSY (Correlation Spectroscopy), HSQC (Heteronuclear Single Quantum Correlation), HMBC (Heteronuclear Multiple Bond Correlation) and ROESY (Rotational nuclear Overhouser Effect Spectroscopy). From a theoretical viewpoint, conformational analysis was done using the molecular mechanics Hyperchem MM2 program. In vitro antiparisitic activity evaluation on Trypanosoma cruzi showed that, at low concentrations, all products present tripanocide activity.